Factors associated with smoking cessation - Samires Avelino de Souza França; Ana Ligian Feitosa das Neves; Tatiane Andressa Santos de Souza; Nandara Celana Negreiros Martins; Saul Rassy Carneiro; Edilene do Socorro Nascimento Falcão Sarges; Maria de Fátima Amine Houat de Souza (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the prevalence and factors associated with smoking abstinence among patients who were treated in a reference unit for smoking cessation. METHODS This cross-sectional study examined the medical records of 532 patients treated in a reference unit for smoking cessation in Belém, PA, Northern Brazil, between January 2010 and June 2012. Sociodemographic variables and those related to smoking history and treatment were analyzed. Statistical significance was set at p < 0.05. RESULTS The mean age of the participants was 50 years; 57.0% of the patients were women. The mean tobacco load was 30 packs/year, and the mean smoking duration was approximately 32 years. Most patients remained in treatment for four months. The rate of smoking abstinence was 75.0%. Regression analysis indicated that maintenance therapy, absence of relapse triggers, and lower chemical dependence were significantly associated with smoking cessation. CONCLUSIONS The smoking abstinence rate observed was 75.0%. The cessation process was associated with several aspects, including the degree of chemical dependence, symptoms of withdrawal, and period of patient follow-up in a multidisciplinary treatment program. Studies of this nature contribute to the collection of consistent epidemiological data and are essential for the implementation of effective smoking prevention and cessation strategies.